O álbum seriado como instrumento de orientação sobre os direitos das crianças - Costa, Lidiane Natalicia (2016)
The Statute of Children and Adolescents (ECA), sanctioned in 1990, still does not apply in full. Given this context, the paper presents an intervention proposal for communication and education about children\'s rights through the flip chart that can be used in several areas, among them, there is the pediatric ward of the Clinical Hospital, field which began the observations and where was raised the need to work the theme and create the product. Illustrations were developed to provide adequate and simple understanding of the Statute of Children and Adolescents. To subsidize the production of the album series, it used the literature, through books and comics. Among the topics discussed were discussed preference that children and adolescents have in the allocation of public resources and the creation of public social policies; the right to education, culture, sports and leisure; right not to be exploited or to work; to be protected, and not have their freedom, dignity and respect violated; access to public health services and social services and the free supply of drugs, prostheses and other resources related to treatment, habilitation or rehabilitation.